Nyaars-morgen, et foredrag - Elbek, Jørgen (Grundtvig-Studier, 1964)
New Year’s Morn By Jørgen Elbek The paper, catalysed by an observation in Paul la Cour’s Diary Fragments, attempts to explicate New Tear’s Morn, G.’s long autobiographical poem. As a preliminary to the analysis a survey of G.’s thoughts about poetic language, later crystalised in his conception of “The Living Word”, is presented. With this background in mind, New Tear’s Morn appears to be G.’s myth of his own life: The mythological elements it includes are more informative than its equivalents in G.’s vita, and its sequence of images is to be taken seriously as an untranslatable language. A. paraphrastic account follows, with special emphasis on the first and the fifth canto. The article concludes that this great poem, as a consequence of its character, was bound to suffer from the break in structure between cantos five and six.